Cold Urticaria and Infectious Mononucleosis in Children - Morais-Almeida, M (2004)
Physical urticaria includes a heterogeneous group of disorders characterized by the development of urticarial lesions and/or angioedema after exposure to certain physical stimuli. The authors present the case of a child with severe acquired cold urticaria secondary to infectious mononucleosis. Avoidance of exposure to cold was recommended; prophylactic treatment with ketotifen and cetirizine was begun and a self-administered epinephrine kit was prescribed. The results of ice cube test and symptoms significantly improved. Physical urticaria, which involves complex pathogenesis, clinical course and therapy, may be potentially life threatening. Evaluation and diagnosis are especially important in children. To our knowledge this is the first description of persistent severe cold-induced urticaria associated with infectious mononucleosis in a child.